ANALISIS SENSOR KAPASITIF PELAT SEJAJAR PADA APLIKASINYA SEBAGAI DETEKSI ZAT SATU FASA DAN MULTI FASA - Fahmi Muhammad Rabbani; Elvan Yuniarti; Mahfudz Al-Huda (Universitas Riau, 2020)
This study uses a pipe/tube-shaped plate capacitive sensor to measure single-phase and multiphase substances to analyze linearity, frequency range, and sensitivity testing. The distance and area of the sensor electrode plate are held constant that and can be viewed from the dielectric material and experimental material. The material or dielectric medium in parallel plate capacitors is a phase consisting of air, aquades, and vegetable oils. Whereas multiphase substances are a combination of air volume, aquades, and vegetable oil. The best linearity analysis results are 0.9467 for aquades + 0.1% NaCl samples and the worst 0.564 for tap-water in layer 1 and the best linearity value is 0.966 for aquades + 0.1% NaCl samples and the most poor 0.5658 is on tap-water at layer 2. The optimal frequency range is at intervals of 500 kHz to 12.5 MHz and the smallest sensitivity test is 500 kHz and the greatest sensitivity is at 12.5 MHz.